Targeting active site residues and structural anchoring positions in terpene synthases - Hou, Anwei; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2021)
The sesterterpene synthase SmTS1 from Streptomyces mobaraensis contains several unusual residues in positions that are otherwise highly conserved. Site-directed mutagenesis experiments for these residues are reported that showed different effects, resulting in some cases in an improved catalytic activity, but in other cases in a loss of enzyme function. For other enzyme variants a functional switch was observed, turning SmTS1 from a sesterterpene into a diterpene synthase. This article gives rational explanations for these findings that may generally allow for protein engineering of other terpene synthases to improve their catalytic efficiency or to change their functions.
Keywords: biosynthesis; enzyme mechanisms; isotopes; site-directed mutagenesis; terpenes

Dictionary of Natural Products

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2016)

(untitled) - Cane, D. E.; Ha, H.-J.; Pargellis, C.; Waldmeier, F.; Swanson, S.; Murthy, P. P. N. (Bioorg. Chem., 1985)

(untitled) - Colby, S. M.; Alonso, W. R.; Katahira, E. J.; McGarvey, D. J.; Croteau, R. (J. Biol. Chem., 1993)

(untitled) - Hua, L.; Matsuda, S. P. T. (Arch. Biochem. Biophys., 1999)

(untitled) - Chou, W. K. W.; Fanizza, I.; Uchiyama, T.; Komatsu, M.; Ikeda, H.; Cane, D. E. (J. Am. Chem. Soc., 2010)

(untitled) - Wise, M. L.; Savage, T. J.; Katahira, E.; Croteau, R. (J. Biol. Chem., 1998)

(untitled) - Rabe, P.; Pahirulzaman, K. A. K.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Starks, C. M.; Back, K.; Chappell, J.; Noel, J. P. (Science, 1997)

(untitled) - Tarshis, L. C.; Yan, M.; Poulter, C. D.; Sacchettini, J. C. (Biochemistry, 1994)

(untitled) - Baer, P.; Rabe, P.; Fischer, K.; Citron, C. A.; Klapschinski, T. A.; Groll, M.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Rinkel, J.; Lauterbach, L.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Rinkel, J.; Lauterbach, L.; Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Lauterbach, L.; Rinkel, J.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Rinkel, J.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Chem. Commun., 2019)

(untitled) - Hou, A.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2020)

(untitled) - Rinkel, J.; Steiner, S. T.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2019)

(untitled) - Zhao, Y. H.; Abraham, M. H.; Zissimos, A. M. (J. Org. Chem., 2003)

(untitled) - Hou, A.; Goldfuss, B.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2021)

(untitled) - Waterhouse, A.; Bertoni, M.; Bienert, S.; Studer, G.; Tauriello, G.; Gumienny, R.; Heer, F. T.; de Beer, T. A. P.; Rempfer, C.; Bordoli, L.; Lepore, R.; Schwede, T. (Nucleic Acids Res., 2018)

(untitled) - Cane, D. E.; Xue, Q.; Fitzsimons, B. C. (Biochemistry, 1996)

(untitled) - Felicetti, B.; Cane, D. E. (J. Am. Chem. Soc., 2004)

(untitled) - Bian, G.; Han, Y.; Hou, A.; Yuan, Y.; Liu, X.; Deng, Z.; Liu, T. (Metab. Eng., 2017)

(untitled) - Meguro, A.; Tomita, T.; Nishiyama, M.; Kuzuyama, T. (ChemBioChem, 2013)

(untitled) - Rinkel, J.; Rabe, P.; Chen, X.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Chem. – Eur. J., 2017)